2009
DOI: 10.1002/col.20524
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the metrics of the perceptual space in a new multistage physiological colour vision model

Abstract: In this work, the metric of a new multistage colour vision model, ATTD05, is assessed and a new colour difference formula is suggested. Firstly, the uniformity of the ATTD05 colour space was compared with that of CIECAM02 for some Munsell samples, because if the model yields a uniform perceptual space, we will be able to implement a colour difference formula as a Euclidian distance between two points. Secondly, we developed a new space based on the perceptual descriptors of the model: brightness, hue, colourfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although the performance of the various color difference equations has been thoroughly tested, it is still unclear which equation is best suitable for high gloss effect coatings with small color differences as used in the automotive industry. Studies show no significant difference in performance between dE CMC and CIEDE2000 or CIE94 . A small preference for CIEDE2000 was found in some other studies, but a statistically significant improvement was only reported in Refs.…”
Section: Some Current Issues In Setting Qc Color Tolerancesmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the performance of the various color difference equations has been thoroughly tested, it is still unclear which equation is best suitable for high gloss effect coatings with small color differences as used in the automotive industry. Studies show no significant difference in performance between dE CMC and CIEDE2000 or CIE94 . A small preference for CIEDE2000 was found in some other studies, but a statistically significant improvement was only reported in Refs.…”
Section: Some Current Issues In Setting Qc Color Tolerancesmentioning
confidence: 87%
“…Studies show no significant difference in performance between dE CMC and CIEDE2000 or CIE94. [12][13][14][15][16][17][18] A small preference for CIEDE2000 was found in some other studies, 8,[19][20][21][22] but a statistically significant improvement was only reported in Refs. 11, 23. Inconsistencies in these results are partly due to the different compositions of the sample sets the equations were tested on.…”
Section: Different Measures For Expressing Tolerancesmentioning
confidence: 99%
“…Since the locus of constant Chroma are more circular (with one exception), the Chroma spacing indexes for all Values and the hue spacing indexes for all Chromas and Values are also lower, and the eccentricity of the centre of gravity for a given Value and the corresponding index of dispersion of the centres of gravity for the rings of the population for that Value are in the some order (again with few exceptions), we conclude that the perceptual space of ATTD05 has a higher degree of uniformity than that of CIECAM02. Consequently, a useful colour difference formula can be implemented [25].…”
Section: Discussionmentioning
confidence: 99%